How do consumers perceive value and price: understanding value-based pricing - Ng, Irene (Henry Stewart Talks, 2009)
How consumers perceive value and price, How companies should go about pricing based on value, The Expected Net Value (ENV) framework, Value proposition and value co-creation, The buyer decision process, Competition: its influence on the ENV, Trading off benefits and outlays, Innovation in reducing expected outlays, Reducing Pareto loss